The Science of Monetary Policy: A New Keynesian Perspective - Clarida, Richard; Galí, Jordi; Gertler, Mark (Journal of Economic Literature, 1999)
The paper reviews the recent literature on monetary policy rules. We exposit the monetary policy design problem within a simple baseline theoretical framework. We then consider the implications of adding various real world complications. Among other things, we show that the optimal policy implicitly incorporates inflation targeting. We also characterize the gains from making a credible commitment to fight inflation. In contrast to conventional wisdom, we show that gains from commitment may emerge even if the central bank is not trying to inadvisedly push output above its natural level. We also consider the implications of frictions such as imperfect information.